Chemistry of 19th Century Lime Mortar on a tabique Pampango (Wattle-and-Daub) from the Philippines - Jan-Michael Cayme (Ge-conservación, 2022)
he chemical characterization of a thick lime mortar coating on a wall construction method in the Philippines called tabique Pampango, or wattle-and-daub method, is reported in this study. The daub material from a 19th century Spanish Colonial Period church convent in Loboc, Bohol, was analyzed using X-ray fluorescence (XRF), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and sieve analysis. These analyses demonstrate that the daub material comprises a largely calcitic binder with clay minerals naturally present in the raw material or clayey soils added intentionally. The presence of clay minerals made the binder hydraulic or hardened through added water. Fine-sized aggregates are abundant in the daub material, making it suitable for non-load bearing applications. This study provided a chemical basis on the construction techniques employed during the colonial period in the Philippines that is useful for advancing conservation work and local historical knowledge.